Design and analysis of passively mode-locked fiber lasers based on saturable absorber for multi-wavelength applications - Jiang, Kai (2017)
Fiber lasers are very promising since they are constructed by inexpensive components (mostly various fibers), highly integrated with flexibly miniaturized cavities, and conveniently collimated output. Mode-locking is the most typical and commonly-used approach to generate ultrafast laser pulses. More and more researchers around the world are researching on this field. This thesis aims at design and analysis passive mode locked fiber lasers based on saturable absorber for multi-wavelength applications. By using single-wall carbon nanotube, we experimentally demonstrate a wavelength-switchable harmonic passive mode locked fiber laser with low pumping threshold and a switchable dual-wavelength mode-locked of thulium-doped fiber laser, the properties of our proposed fiber lasers become potential candidate for the molecular spectroscopy, optical communication, and biomedical applications.